CAUSES AND BARRIERS TO INHERITANCE IN ISLAMIC LAW - Sakban Lubis (Proceeding International Seminar of Islamic Studies, 2021)
Islamic law is the law of Allah Almighty, and as the law of God he demands obedience from the Muslim ummah to carry it out as a continuation of faith in Allah, one of the rulings to be implemented is the ruling of the Islamic heirs. In the inheritance there is one very important point about who is entitled to inherit and anyone who is not entitled to receive an inheritance from al-marhum. The obstacle to receiving inheritance (mawani' al-irts) is one of the important sub-languages in the discourse of Islamic inheritance law. It is closely related to other sub-languages which are the stages of selection of beneficiaries before the calculation and division is carried out, namely selection based on family relationships that rest on two lines of relationship, namely: blood relations and legitimate marital relationships. At this stage, families who do not pass the selection, such as brother-in-law and son-in-law, are eliminated by themselves. The next selection is not entitled to receive inheritance some things, At this stage, prospective beneficiaries who do not pass the sekeksi, such as taking a life, or different religions with people who would bequeath property to him (muwarrits) become eliminated by itself, and slavery causes no inheritance.Keywords: Causes, Barriers, Heritage, Law, Islam